Balanced cathodic debromination and hydrogen evolution reactions endow highly selective epoxidation of styrene. (November 2022) - Zhang, Yuchi; Iqbal, Asma; Zai, Jiantao; Li, Wenqian; Guo, Hongran; Meng, Xiang; Li, Wenjing; Islam, Ibrahim ul; Xin, Zhiling; Qian, Xuefeng
Abstract: The olefin epoxidation is a significant conversion that has sparked the scientific community's interest due to the importance of epoxide in the chemical industry. Conventional techniques produce hazardous oxidants and necessitate hard operating conditions and complicated separation processes. Electro-epoxidation based on Br − /Br2 is considered as an eco-friendly method, while unsatisfied electrode performance limits their selectivity and Faraday efficiency. Here, we develop an economical and highly selective electrochemical strategy for styrene epoxidation using acid and heat modified graphite felt (AHGF) electrodes, which exhibit abundant electrochemical active sites for superior anodic bromide oxidation and facilitated cathodic debromination. After optimizing reaction conditions, we obtain a 99% selectivity of styrene oxide with a Faraday efficiency (FE) of 89% at 30 mA. We discover that the remarkable performance results from the balanced cathodic debromination and hydrogen evolution reactions (HER). We explore this strategy on various styrene-based substrates and believe it has great potential for industrial applications. Highlights: Electrochemical epoxidation is facilitated via cathodic debromination. Excellent selectivity of 99% was achieved with acid and heat modified graphite felts. Outstanding Faraday efficiency (89%) and energy intensity (0.14 kW. h per 1 mol styrene oxide) for mass production potential